Validation and Application of Sand Pile Modeling of Multiseeded HTS Bulk Superconductors - Murta-Pina, Joao (2017)
This work was supported by national funds through FCT Fundacao para a Ciencia e a Tecnologia, under project PEst-OE/EEI/UI0066/2011